Công văn của Bộ Công thương về việc trả lời chất vấn của Đại biểu Đinh Duy Vượt (Số: 11713/BCT-KH) - Bộ Công thương (2016)
Công văn của Bộ Công thương về việc trả lời chất vấn của Đại biểu Đinh Duy Vượt (Số: 11713/BCT-KH) ngày 06/12/2016